Analisis Faktor yang Memengaruhi Produksi Usahatani Kunyit di Desa Bandilan Kecamatan Prajekan Kabupaten Bondowoso - Mayangsari, Andina; Wijaya, Rifky Agnitian; Mufid, Ahmad (Universitas Galuh, 2024)
The aim of this research is to identify factors that influence production in the turmeric farming sector and evaluate the scale of production in Bandilan Village, Prajekan District, Bondowoso Regency. The data used includes primary information obtained directly from farmers, including variables such as name, age, education level, land area, number of seeds used, and type of labor. Secondary data was also obtained from various agencies and institutions, including the Central Statistics Agency (BPS). This research involved all turmeric farmers in Bandilan Village, Prajekan District, with a total of 50 respondents, which is a saturated sample. The data analysis method used is the Cobb-Douglas production function model with the help of SPSS software. The research results show that based on the Cobb-Douglas production function analysis, turmeric farming in Bandilan Village, Prajekan District, Bondowoso Regency, is significantly influenced by the area of land used. Simultaneously, all observed variables have a significant influence on turmeric production. Apart from that, the production scale of turmeric farming in Bandilan Village, Prajekan District, Bondowoso Regency, was found to be in a condition of Increasing Return to Scale.